Intraorbital Steroid Injection for Active Thyroid Ophthalmopathy - Abbas Bagheri; Mohammad Abbaszadeh; Shahin Yazdani (Journal of Ophthalmic & Vision Research, 2020)
Purpose: To evaluate the effect of orbital steroid injections in patients with active thyroid ophthalmopathy resistant to or dependent on systemic steroids, or with complications related to systemic steroid use. Methods: This prospective non-comparative case series includes 31 eyes of 17 patients with active thyroid ophthalmopathy and clinical activity score (CAS) of 3 or more, without compressive optic neuropathy or overt exposure keratopathy. All subjects had a history of previous systemic steroid use (with steroid resistance or dependence) or had developed complications related to steroids. A combination of steroids including triamcinolone acetonide 20 mg and dexamethasone 4 mg was injected in the upper and lower retroseptal orbital spaces three or four times at one-month intervals. The patients were examined periodically after each injection and at least three months after the last injection. Results: Mean pre-injection CAS was 5.2